SCHIFF BASES AND THEIR COMPLEXITIES: A REVIEW - Abdul-Bary, Mariam; Sweah, Zainab J. (Journal for Technology and Science, 2026)
Objective: H. Schiff of Germany made the first attempts at preparing the Schiff bases in 1864, first showing that primary aliphatic or aromatic amines could react with ketones or aldehydes to form condensed monoalkyl or monoaryl imines with little change in the stereochemistry of the carbonyl carbon. The identification of this led to a long history of development of Schiff base research, which prompted chemists to find novel analogues that have better biological and therapeutic properties. Method: When Schiff bases are complexed with metallic ions, they often form very stable complexes that have shown promising antibacterial, antifungal, and anticancer effects. They can play an important role in coordination chemistry, largely because the azomethine (C=N) functional group has a strong binding capacity and is able to interact with a large range of metal ions, especially transition metal ions. Results: Schiff bases have the azomethine motif (C=N-R2) structurally and can be made highly reactive with the inclusion of heterocyclic compounds like pyrazole or imidazole. Novelty: A combination of these rings with the Schiff base skeleton frequently leads to the production of compounds which exhibit significant antifungal properties.